ChemInform Abstract: Controllable Growth of SnS2/SnO2 Heterostructured Nanoplates via a Hydrothermal‐Assisted Self‐Hydrolysis Process and their Visible‐Light‐Driven Photocatalytic Reduction of Cr(VI). Issue 48 (2nd December 2014) - Mao, Liyuan; Li, Jingjing; Xie, Yunlong; Zhong, Yijun; Hu, Yong
Abstract A series of SnS2/SnO2 heterostructured nanoplates with different SnO2 contents are synthesized by self‐hydrolysis of SnS2 nanoplates (obtained from aqueous mixtures of SnCl4 and thiourea, autoclave, 180 °C, 10 h) in the presence of an aqueous citric acid solution (autoclave, 180 °C, 2—24 h).